2004
DOI: 10.1093/ajcn/79.4.669
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a gluten-free diet on gastrointestinal symptoms in celiac disease

Abstract: Celiac disease causes a wide range of gastrointestinal symptoms. Clinicians must have a high level of suspicion to detect the atypical forms of celiac disease. With a gluten-free diet, patients have substantial and rapid improvement of symptoms, including symptoms other than the typical ones of diarrhea, steatorrhea, and weight loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
159
0
8

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(178 citation statements)
references
References 17 publications
11
159
0
8
Order By: Relevance
“…However, the early recognition and treatment of CD are recommended, as glu- Dickey et al 30 57 EmA 6 (11%) 4 (7%) Kingham et al 31 67 -4 (6%) 4 (6%) Gillett et al 32 378 tTGA, EmA 11 (2.6%) 5 (1.3%) Floreani et al 33 87 EmA 3 (3.4%) 3 (3.4%) Volta et al 34 173 tTGA, EmA 7 (4%) 7 (4%) Chatzicostas et al 35 62 tTGA, EmA 6 (10%) 0* Bardella et al 36 65 AGA, EmA 0 -Niveloni et al 37 10 AGA, EmA ten restriction improves the symptoms attributable to CD and can also reduce the risk of complications (malabsorption, osteoporosis, and malignant neoplasms). 44,45 Autoimmune Hepatitis (AIH) Prevalence. Two studies found that the prevalence of CD in patients with AIH was 4% to 6.4%.…”
Section: Primary Biliary Cirrhosismentioning
confidence: 99%
See 2 more Smart Citations
“…However, the early recognition and treatment of CD are recommended, as glu- Dickey et al 30 57 EmA 6 (11%) 4 (7%) Kingham et al 31 67 -4 (6%) 4 (6%) Gillett et al 32 378 tTGA, EmA 11 (2.6%) 5 (1.3%) Floreani et al 33 87 EmA 3 (3.4%) 3 (3.4%) Volta et al 34 173 tTGA, EmA 7 (4%) 7 (4%) Chatzicostas et al 35 62 tTGA, EmA 6 (10%) 0* Bardella et al 36 65 AGA, EmA 0 -Niveloni et al 37 10 AGA, EmA ten restriction improves the symptoms attributable to CD and can also reduce the risk of complications (malabsorption, osteoporosis, and malignant neoplasms). 44,45 Autoimmune Hepatitis (AIH) Prevalence. Two studies found that the prevalence of CD in patients with AIH was 4% to 6.4%.…”
Section: Primary Biliary Cirrhosismentioning
confidence: 99%
“…Again, treatment with a GFD is necessary to improve symptoms of CD (if present) and to avoid severe chronic complications of CD. 44,45 Primary Sclerosing Cholangitis…”
Section: Primary Biliary Cirrhosismentioning
confidence: 99%
See 1 more Smart Citation
“…Other several studies were established subsequently about this relationship (7). The effect of GFD on natural history of AIH is not clear but GFD is necessary to improve the symptoms of CD (25).…”
Section: Discussionmentioning
confidence: 99%
“…Especially, with rising number of patients with gluten sensitivity and celiac disease [2]. In addition to, the rapid change in consumer lifestyle, where gluten-free diet is also associated with weight management and overall health [3,4].…”
Section: Introductionmentioning
confidence: 99%